2x + 4x - 45 = x + 9 --> (simplified) 6x - 45 = x + 9
you need to get x on one side. im gonna put it to the left since its easier (which side you move it to doesn't matter that much).
so you need to cancel out the x on the right (x + 9). we do this by subtracting x (or 1x) on both sides. our equation now looks like 5x - 45 = 9.
now we need to move our non-variable to the right. we do this by adding 45 on both sides. our equation now looks like 5x = 54.
we need to divide 54 by 5 so that x is alone. 54/5 = 10.8. x = 10.8